FOCUS GROUP DISCUSSION: A TOOL FOR QUALITATIVE INQUIRY - Basnet, Hom Bahadur (Researcher: A Research Journal of Culture and Society, 2018)
This article focused on to explore the concept, use, strengths and weakness of focus groups discussion. It also provides the ideas about searching qualitative information in field setting. This tool has the potential to become a central approach in sociological and educational research, whether focused on the pragmatic end of evaluation or the abstract goal of theory building. Moreover, focus group discussion is an efficient and effective way to gain insights into social process. During focus group discussion, the moderator facilitates all informants in active participation and dig out the richer information. Researcher: A Research Journal of Culture and Society Vol. 3, No. 3, January 2018, Page: 81-88